2001 Aboriginal Peoples Survey Community Profiles [Canada] [HTML] - Statistics Canada. Social and Aboriginal Statistics Division (Borealis, 2003)
Thee profiles contain free information on adult and child Aboriginal identity population for selected communities in Canada where the Aboriginal identity population is 200 or more according to the 2001 Census. These communities include First Nations, Métis settlements, Inuit communities, urban centres and rural areas. Data for Nisga’a communities are aggregated to the Nisga'a Nation level as are data for communities that are part of the Grand Council of the Crees. Not all First Nations communities could be included in the sample due to operational constraints. As well, some communities chose not to participate. The tables are Archived Statistics Canada webpages Access data here